Antiresorptive agents enhance ossification of free flap reconstructions of the mandible: a radiological retrospective cohort study - Gottsauner, Maximilian; Meier, Johannes; Eichberger, Jonas; Eckmüller, Stephanie; Schuderer, Johannes; Fiedler, Mathias; Maurer, Michael; Reichert, Torsten E.; Ettl, Tobias (Frontiers in Oncology, 2024)
Background: The aim of this study was to investigate the effect of antiresorptive agents on ossification of reconstructed mandibles by free bone grafts for the first time.Methods: 38 reconstructions of the jaw were retrospectively evaluated for ossification between bone segments by two raters based on postoperative panoramic radiographs.The study group (n=13) had segmental resection of the mandible and free bone flap reconstruction due to medication related osteonecrosis of the jaw (MRONJ). The control group (noMRONJ, n=25) comprised segmental mandibular resections and free bone flap reconstructions due to tumor, chronic osteomyelitis or trauma without any radiation. Ossification time and influencing factors were evaluated. Results: Both duration of surgery (346±90 min. vs. 498±124 min.; p<0.001) and hospitalization (8.7±2.8 days vs. 13.4±5.3 days, p=0.006) were shorter in the MRONJ group compared to the noMRONJ group. Ossification after mandibular reconstruction was significantly faster in the MRONJ study group (224 days, IQR 175-287) compared to the control group (288 days, IQR 194-445; p<0.001). Moreover, a good initial contact between the segments resulted in faster ossification (p<0.001) in the MRONJ group.Ossification rate between original and grafted bone or between grafted bone segments only did not differ in both the study and the control group (MRONJ p=0.705 vs. control p=0.292). Type of antiresorptive agent did not show any significance for ossification.The rate of wound healing disturbances did also not differ between the study and the control group (p=0.69) Conclusion: Advanced MRONJ (stage 3) can be resected and reconstructed safely with free microvascular bone flaps. Antiresorptive agents enhance ossification of the bony segments. Optimal initial contact of the bone segments accelerates bone healing.Surgery and hospitalization are markedly shortened in this vulnerable group of MRONJ patients compared to oncologic patients.